2018
DOI: 10.1016/j.marpolbul.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Marine animal forests as useful indicators of entanglement by marine litter

Abstract: Entanglement of marine fauna is one of the principal impacts of marine litter, with an incidence that can vary strongly according to regions, the type and the quantity of marine litter. On the seafloor, areas dominated by sessile suspension feeders, such as tropical coral reefs or deep-sea coral and sponge aggregations, have been termed "animal forests" and have a strong potential to monitor the temporal and spatial trends of entanglement by marine litter, especially fishing gears. Several characteristics of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 32 publications
3
36
0
Order By: Relevance
“…Although the deep marine environment is considered a hostile environment, difficult to access and requiring considerable resources, marine litter studies have become critical in order to better protect the deep Mediterranean ecosystem, and support targeted and effective actions for its preservation (Consoli et al, 2018). To achieve this, opportunistic approaches are well-adapted.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the deep marine environment is considered a hostile environment, difficult to access and requiring considerable resources, marine litter studies have become critical in order to better protect the deep Mediterranean ecosystem, and support targeted and effective actions for its preservation (Consoli et al, 2018). To achieve this, opportunistic approaches are well-adapted.…”
Section: Discussionmentioning
confidence: 99%
“…Every year in the world, 8 million of tons of solid plastic debris are introduced into the marine ecosystem (Jambeck et al, 2015;UNEP/MAP, 2015;Villarrubia-Gómez et al, 2018), and their increasing amounts and low degradation rates lead to 2 accumulation in the oceans where they cause a serious threat to the marine environment, human health and the economy (Barnes et al, 2009;Brouwer et al, 2017;Ioakeimidis et al, 2017;Ioakeimidis et al, 2014). Numerous studies have shown the diversity of harm inflicted, which includes in particular the strangling of organisms (Adimey et al, 2014;Anderson and Alford, 2014;Galgani et al, 2018), the ingestion of litter (Fossi et al, 2018;Galgani et al, 2014), the rafting of invasive species (Carlton et al, 2017), and the production of Persistent Organic Pollutants (POP) (Engler, 2012). The problem of marine litter is ubiquitous, concerns all sizes of litter, extending into environmental compartments ranging from shorelines to deeper areas (Thompson et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…threaten these vulnerable bioconstruction systems, as well as climate change and the spread of alien species (Ballesteros, 2006;Coll et al, 2010;Piazzi et al, 2012). In particular, the widespread presence of marine litter represents one of the most important threats to biogenic reefs, which leads to a degradation of these habitats (de Carvalho-Souza et al, 2018) and the associated organisms (Galgani et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, in Cassidaigne canyon, the surface corresponding to M. oculata rubble was measured as 15% of the total surface occupied by the species. It is known that fishing longlines can have impacts on colonies due to entanglement and physical breakage (Lastras et al, 2016;D'Onghia et al, 2017;Fanelli et al, 2017;Galgani et al, 2018). Yet, in Cassidaigne canyon, the locations Cassis-200 and Cassis-500 have been included within regulated fisheries zones since 2012.…”
Section: Marine Litter and Waste Disposalmentioning
confidence: 99%